FAKTOR-FAKTOR YANG MEMPENGARUHI MATERNAL SELF-EFFICACY PADA IBU POSTPARTUM DI MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS PEJUANG - BEKASI - Desiana Rachmawati, (2021)
Maternal self-efficacy is part of the concept of self-efficacy in the form of the mother's perception or view of her ability to carry out her duties and roles as parents in caring for and raising babies optimally faced with all situations. The purpose of this study was to determine the dominant factors that influence maternal self-efficacy in postpartum mothers during the COVID-19 pandemic in the Pejuang Health Center work area of Bekasi City. The research design used was cross sectional with 116 samples and the sampling technique used was accidental sampling. Data was collected through a questionnaire consisting of four parts, namely MSE, WDEQ-B, MSPSS, PSAS-RSF-C and then analyzed by multiple logistic regression. The results of the bivariate test showed a significant relationship with MSE, namely the variables of education level, parity, childbirth experience, social support, and anxiety (p value < 0.05). The dominant factor that affects MSE analyzed by multiple logistic regression is social support (p value = 0.004 , OR = 2.366). It is hoped that health services will pay more attention to and examine psychological aspects, especially for postpartum mothers in the midst of the COVID-19 pandemic which can affect maternal self-efficacy. Further research can continue experimental studies, especially related to interventions to increase maternal self-efficacy in postpartum mothers.